How Well Does Western Environmental Theory Explain Crime in the Arabian Context? The Case Study of Riyadh, Saudi Arabia. (March 2019) - Alotaibi, Nawaf Ibrahim; Evans, Andrew J.; Heppenstall, Alison J.; Malleson, Nicolas S.
Crime within Arabic countries is significantly different from Western crime in type, frequency, and motivation. For example, motor vehicle theft (MVT) has constituted the largest proportion of property crime incidents in Saudi Arabia (SA) for decades. This is in stark contrast to Western countries where burglary and street theft dominate. Environmental criminology theories, such as routine activity theory and crime pattern theory, have the potential to help to investigate Arabic crime. However, there is no research that has sought to evaluate the validity of these theories within such a different cultural context. This article represents a first step in addressing this substantial research gap, taking MVT within SA as a case study. We evaluate previous MVT studies using an environmental criminology approach with a critical view to applying environmental criminology to an Arabic context. The article identifies a range of key features in SA that are different from typical Western contexts. These differences could limit the appropriateness of existing methodologies used to apply environmental criminology. The study also reveals that the methodologies associated with traditional environmental crime theory need adjusting more generally when working with MVT, not least to account for shifts in the location of opportunities for crime with time.